Cold air outbreaks over high-latitude sea gulfs - H. I. Savijärvi (Tellus: Series A, Dynamic Meteorology and Oceanography, 2012)
Wintertime cold outbreaks were studied via a 2-D numerical model set across an 80 km wide non-frozen sea gulf along 60°N (‘Gulf of Finland’). In calm conditions, land breezes develop over both coasts with relatively large along-shore wind components. The mid-gulf convergence of the colliding land breezes leads to a moderate rising motion at about 600 m height, forcing bands of low cloud and snowfall along the gulf, whereas the near-surface horizontal wind shear may induce ‘mini-hurricanes’. A weak large-scale cold outbreak across the gulf distorts the land breeze cells, damping the rising motion, whereas a moderate cross-coast outbreak modifies them into a typical heat island circulation pattern with only a modest rising motion over a flat windward shore. A cold outbreak along the non-frozen gulf leads to strong heat transfer from the sea. This maintains the embedded coastal land breeze circulations that contribute to a double low-level jet structure. The strongest rising motion was obtained for surface winds blowing along the gulf. It is suggested that the Swedish Gävle snowstorm of December 1998 was such a case.